Bridging Classical and Revised Reinforcement Sensitivity Theory Research: A Longitudinal Analysis of a Large Population Study - Espinoza Oyarce, Daniela A.; Burns, Richard; Butterworth, Peter; Cherbuin, Nicolas (Frontiers in Psychology, 2021)
The reinforcement sensitivity theory (RST) proposes that neurobiological systems mediate protective and appetitive behaviours and the functioning of these systems is associated to personality traits. In this manner, the RST is a link between neuroscience, behaviour, and personality. The theory evolved to the present revised version describing three systems: fight-flight-freezing, behavioural approach/activation (BAS), and behavioural inhibition (BIS). However, the most widely available measure of the theory, the BIS/BAS scales, only investigates two systems. Using a large longitudinal community survey, we found that the BIS/BAS scales can be re-structured to investigate the three systems of the theory with a BIS scale, three BAS scales, and a separate fight-flight-freezing system (FFFS) scale. The re-structured scales were age, sex, and longitudinally invariant, and associations with personality and mental health measures followed theoretical expectations and previously published associations. The proposed framework can be used to investigate behavioural choices influencing physical and mental health and bridge historical with contemporary research.